PSYCHOLOGICAL AND PEDAGOGICAL PROBLEMS OF FORMATION OF PROFESSIONAL ORIENTATION OF PRIMARY SCHOOL STUDENTS IN PEDAGOGICAL THEORY AND PRACTICE (Pedagogy of Higher and Secondary Education, 2008)
The article reveals modern psycho-pedagogical problems professional orientation of primary school students in pedagogical theory and practice.